Comparison of coronary risk factors and angiographic findings in younger and older patients with significant coronary artery disease - Mahjoob Mohammad Parsa; Sadeghi Soheila; Khanaman Hamide Falahaty; Naderian Mohammadreza; Khaheshi Isa (Sciendo, 2018)
Background. Coronary artery disease (CAD) is uncommon among young adults and may have certain characteristics that are different from those in older patients. The aim of the current study was to determine the risk factors of CAD, important laboratory data and angiographic findings in young patients with CAD and to compare them with the old patients.